2002
DOI: 10.1080/08941930290086010
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Influence of Tissue Engineering Techniques on Tracheal Strength: An Experimental Study on Sheep Trachea

Abstract: Tissue engineering is an attractive concept for facilitating the transplantation of different tissue types with a low immunogeneity and a well-preserved tissue structure. We examined the influence of treatment with trypsin/ethylenediamine tetraacetic acid (EDTA) on the mechanical properties of tracheae. Fresh sheep tracheae were stored in a trypsin/EDTA solution for various periods of time (24, 46, and 72 h) and their breaking strength was subsequently examined. The results were compared with native trachea. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Indeed, while ECM components may be similar across a range of tissues, each tissue has its own distinct combination of macromolecules that provide the necessary cellular cues [6,27]. Negative results with decellularized porcine tracheas were mainly related to the decellularization protocol used, which causes reduction of ECM content, compromising the ability of the scaffold to provide mechanical support during the remodelling process [9,26,28]. The detergentenzymatic method (DEM) [17], instead, appears to be a superior decellularization approach than other methods, as it achieves a complete decellularization while preserving tissue matrix integrity and biomechanical properties [29].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, while ECM components may be similar across a range of tissues, each tissue has its own distinct combination of macromolecules that provide the necessary cellular cues [6,27]. Negative results with decellularized porcine tracheas were mainly related to the decellularization protocol used, which causes reduction of ECM content, compromising the ability of the scaffold to provide mechanical support during the remodelling process [9,26,28]. The detergentenzymatic method (DEM) [17], instead, appears to be a superior decellularization approach than other methods, as it achieves a complete decellularization while preserving tissue matrix integrity and biomechanical properties [29].…”
Section: Discussionmentioning
confidence: 97%
“…Sachs et al 81 found primary human tracheal epithelial cells cultured in media with high concentration of retinoic acid produced better cell differentiation when compared with media with low or no retinoic acid. Behrend et al 82 addressed the challenge of treating non-human tissue such that low immunogeneity on transplantation is achieved while preserving the tissue's structural integrity. Results showed that trypsin/EDTA tissue preparation caused a substantial reduction in the tensile strength of the trachea, making this an unsuitable method for preparing tracheal tissue intended for transplantation.…”
Section: Tissue Preparations and Culture Mediamentioning
confidence: 99%
“…Results showed that trypsin/EDTA tissue preparation caused a substantial reduction in the tensile strength of the trachea, making this an unsuitable method for preparing tracheal tissue intended for transplantation. 82 In a study by Conconi et al 83 porcine tracheal matrices were treated with a detergent-enzymatic method to reduce the an- In another experiment, autologous costal chondrocytes, smooth muscle cells, respiratory epithelium, and endothelial progenitor cells were cultured in vitro and then seeded on acellularized jejunal segments that served as a vascularized matrix. Chondrocyte growth and extracellular cartilaginous matrix production were observed within 2 weeks and thus this experiment yielded the fundamental elements for a tissueengineered trachea (TET).…”
Section: Tissue Preparations and Culture Mediamentioning
confidence: 99%
“…The main goal of the decellularization approach is to remove most or all of the cellular and nuclear material from the tissue/organ (making substitutes nonimmunogenic), without or only minimally altering the composition, biological activity, and mechanical integrity of the remaining ECM. Different decellularization protocols have been evaluated to obtain tracheal grafts, and most were highly efficient in removing cellular materials but cause disruption of glycosaminglycans and substantially reduced laminin and fibronectin ECM content, compromising the ability of the scaffold to provide mechanical support during the remodeling process [56][57][58]. Using a detergent-enzymatic method (DEM) (Fig.…”
Section: Scaffoldmentioning
confidence: 99%